2017
DOI: 10.1590/1807-1929/agriambi.v21n9p628-633
|View full text |Cite
|
Sign up to set email alerts
|

Potassium fertilization in the cultivation of colored cotton irrigated with saline water

Abstract: A B S T R A C TThe objective of this study was to evaluate growth, flowering and production components of the cotton cv. 'BRS Topázio' irrigated with water of different salinity levels and potassium (K) doses in the soil. The research was conducted in a greenhouse. The experiment was set in a randomized complete block design with four replicates, in 4 x 4 factorial arrangement with 4 levels of irrigation water salinity (1.5, 3.0, 4.5 and 6.0 dS m -1 ) and four K doses (50, 75, 100 and 125% of the recommendatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Thus, it is clear that, under high salinity levels, the supply of 45/45% of K 2 O/P 2 O 5 had mitigating action on chlorophyll a synthesis, possibly because the increase in the supply of mineral fertilizers contributes to the increase in soil EC, given their salt indices, especially that of potassium chloride, compromising chlorophyll biosynthesis by crops. This situation has been observed in cowpea (Prazeres et al, 2015), colored cotton (A. R. Silva et al, 2017), and West Indian cherry (Dias et al, 2019) under water salinity conditions.…”
Section: Second Production Cycle (A) and The Second (B) Production Cymentioning
confidence: 66%
See 1 more Smart Citation
“…Thus, it is clear that, under high salinity levels, the supply of 45/45% of K 2 O/P 2 O 5 had mitigating action on chlorophyll a synthesis, possibly because the increase in the supply of mineral fertilizers contributes to the increase in soil EC, given their salt indices, especially that of potassium chloride, compromising chlorophyll biosynthesis by crops. This situation has been observed in cowpea (Prazeres et al, 2015), colored cotton (A. R. Silva et al, 2017), and West Indian cherry (Dias et al, 2019) under water salinity conditions.…”
Section: Second Production Cycle (A) and The Second (B) Production Cymentioning
confidence: 66%
“…BRS 366 Jaburu. Sousa, Gheyi, Brito, Silva and Lima (2017), in a study with citrus under irrigation with saline water, found a reduction of 38.81% in carotenoid contents as salinity levels increased from 0.6 to 3.0 dS m -1 .…”
Section: Second Production Cycle (A) and The Second (B) Production Cymentioning
confidence: 95%
“…In the literature, studies involving salinity in cotton usually report the negative effects of salt on plant growth, even at electrical conductivity values lower than those used in the present study. Silva et al (2017) subjected the cultivar BRS Topázio to salinity at the ECw of 6 dS m -1 for 53 to 108 days and found moderate tolerance based on the variables used. The height reduction in plants ranged from 32% to 46% after 53 and 108 days of stress, respectively.…”
Section: Growth Of the Cultivars Under Salt Stressmentioning
confidence: 99%
“…However, the salt concentrations that cause reduction in growth and post-harvest fruit quality of West Indian cherry may vary among species and cultivars, which exhibit different physiological behaviors regarding the effects of the stress caused by water and/or soil salinity. These effects depend on crop development stage, duration of exposure to stress, type of salt present in the medium, environmental conditions, cultural and irrigation managements, edaphoclimatic conditions and fertilization (SILVA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%